Use of non-thermal plasma associated with enzymatic hydrolysis to obtain xylo-oligosaccharides (XOS) from brewery by-product - Pereira, Gabriela Nayana (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Alimentos, Florianópolis, 2022.